Emerging role of glial cells in the control of body weight - Cristina García‐Cáceres; Esther Fuente-Martín; Jesús Argente; Julie A. Chowen (2012)
Glia are the most abundant cell type in the brain and are indispensible for the normal execution of neuronal actions. They protect neurons from noxious insults and modulate synaptic transmission through affectation of synaptic inputs, release of glial transmitters and uptake of neurotransmitters from the synaptic cleft. They also transport nutrients and other circulating factors into the brain thus controlling the energy sources and signals reaching neurons. Moreover, glia express receptors for metabolic hormones, such as leptin and insulin, and can be activated in response to increased weight gain and dietary challenges. However, chronic glial activation can be detrimental to neurons, with hypothalamic astrocyte activation or gliosis suggested to be involved in the perpetuation of obesity and the onset of secondary complications. It is now accepted that glia may be a very important participant in metabolic control and a possible therapeutical target. Here we briefly review this rapidly advancing field.